2010
DOI: 10.1063/1.3293439
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for random networks of diodes in thin films of LaVO3 on SrTiO3 substrates

Abstract: Articles you may be interested inOxygen vacancies-induced metal-insulator transition in La2/3Sr1/3VO3 thin films: Role of the oxygen substrate-to-film transfer Evidence of direct correlation between out-of-plane lattice parameter and metal-insulator transition temperature in oxygen-depleted manganite thin films Appl. Phys. Lett. 100, 042404 (2012); 10.1063/1.3676268 Magnetotransport properties of c -axis oriented La 0.7 Sr 0.3 MnO 3 thin films on MgO-buffered SiO 2 / Si substrates J. Appl. Phys. 105, 07D711 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…22 The stabilization of the perovskite LaVO 3 phase in thin films was successful by performing the growth in either high vacuum 4,5,[7][8][9]22 or in pure Ar or Ar/H 2 atmosphere. 9,21 We fabricated the films by PLD using a KrF excimer laser. The chamber was evacuated down to less than 10 −7 mbar.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…22 The stabilization of the perovskite LaVO 3 phase in thin films was successful by performing the growth in either high vacuum 4,5,[7][8][9]22 or in pure Ar or Ar/H 2 atmosphere. 9,21 We fabricated the films by PLD using a KrF excimer laser. The chamber was evacuated down to less than 10 −7 mbar.…”
mentioning
confidence: 99%
“…Epitaxial growth of LaVO 3 films has been achieved by a variety of techniques, predominantly by PLD 4,5,[7][8][9]21 or by molecular beam epitaxy. 22 The stabilization of the perovskite LaVO 3 phase in thin films was successful by performing the growth in either high vacuum 4,5,[7][8][9]22 or in pure Ar or Ar/H 2 atmosphere.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We can rule out heating as a source of nonlinearity in the low temperature I-V curves by performing a Joule heating analysis similar to the one reported in Padhan et al 51 (see Supplemental Materials for details). Razavi et al reported similar upturns in resistivity and non-linear I-V characteristics at low temperature, they attributed it to the formation of random diode networks in their LVO thin films 52 . They report that the observed nonlinear behavior happened only in the films with relatively small values for c (close to that of the STO substrate) and it would disappear when the films be-come insulating as the lattice parameter of the film became larger (1% larger than that of STO).…”
Section: Resistivitymentioning
confidence: 84%